Jumping performance profile of male and female gymnasts - Marina, M.; Jemni, M.; Rodriguez, F. (The Journal of Sports Medicine and Physical Fitness, 2013)
Aim: The aim of this study was to establish a more precise jumping performance profile of elite gymnasts than that published in previous studies. Methods: Seventy-six elite male and female competitive gymnasts and 91 moderately active subjects volunteered for the study. The jumping tests performed on a contact mat were: squat jump (SJ) with progressive loads of 0%, 25%, 50 %, 75% and 100% of body mass, counter-movement jump (CMJ), and counter-movement jump with arm swing (CMJA). The parameters used to assess the jumping performance were flight time (FT, ms), FT normalized to body mass (FTbm, ms/kg), estimated elastic component (EC) and arm participation (AP). In SJ, the overload with respect to body mass had a negative impact on reliability in all of the subgroups that were analysed. When overloads were above 50% of body mass in SJ, reliability was poor. Therefore, overloads should not be used with sedentary young females. Gymnasts carry out a large number of jumps from very young ages, which may explain their high jump reliability (ICC>0.91). Results: We used FT to estimate the F-v curve through SJ with overloads. The curves for male gymnasts and their controls were practically identical. However, when FT was normalized to body mass (FTbm), the F-v curve showed the advantage of female gymnasts in particular over their control group when overloads were above 50%. Larger, more significant (PConclusion: The better AP of the gymnasts (+79%) may be due to better arm strength conditioning and segmental coordination. EC and AP can be considered a suitable complementary parameter of jumping performance in gymnasts.